2018
DOI: 10.1002/tea.21469
|View full text |Cite
|
Sign up to set email alerts
|

Teaching practices linked to the implementation of inquiry‐based practical work in certain science classrooms

Abstract: Around the world, there have been curricula reforms involving the incorporation of the inquiry‐based teaching and learning strategy in secondary school science education in general and in practical work in particular. Research in inquiry‐based practical work (IBPW) has focused, for example, on aspects of the strategy itself, on teacher professional development, and on classroom teaching and learning based on the strategy. However, the question of the extent to which teaching practices linked to the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
(57 reference statements)
4
20
1
1
Order By: Relevance
“…It is most likely, teachers did not perceive practical work as a means of improving learners' knowledge and process skills (Swain et al, 2013). These observations concur with Flick andLederman (2006), Effendi-Hasibuan andMukminin (2019), and Akuma and Callaghan (2019) revealed that teachers experienced challenges in implementing explicit and implicit inquiry teaching in the classroom. Besides, teachers indicated that they lacked the resources to conduct practical work.…”
Section: Teachers' Motives Of Conducting Practical Worksupporting
confidence: 88%
“…It is most likely, teachers did not perceive practical work as a means of improving learners' knowledge and process skills (Swain et al, 2013). These observations concur with Flick andLederman (2006), Effendi-Hasibuan andMukminin (2019), and Akuma and Callaghan (2019) revealed that teachers experienced challenges in implementing explicit and implicit inquiry teaching in the classroom. Besides, teachers indicated that they lacked the resources to conduct practical work.…”
Section: Teachers' Motives Of Conducting Practical Worksupporting
confidence: 88%
“…Because teacher feedback in part creates school climate (Thapa et al, ), there are whole‐school yields in encouraging and supporting all teachers in their consistent use of growth feedback. It is important to note however that researchers who have tested interventions and programs that target teacher feedback (Akuma & Callaghan, ; Voerman, Meijer, Korthagen, & Simons, ) and school climate (Bradshaw, Koth, Thornton, & Leaf, ) have noted considerable challenges to long‐term change, such as implementation fidelity and resistance to change. As such, it is important for teachers and school‐leaders to consider approaches to growth feedback (such as those suggested here) that can be sustained and used consistently.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of traditional instruction is a major contributor to the low scientific literacy in Africa (e.g., Anamuah-Mensah, 2012;Shumba, 1999). In attempts to address the low scientific literacy, inquiry-based science teaching and learning is emphasized as the current curricula rationale for basic science education in many African countries (e.g., Akuma & Callaghan, 2019;Athuman, 2017;Chabalengula & Mumba, 2012;Leon, 2012;Ssempala, 2017). Inquiry instruction is a contemporary global approach for developing students' scientific literacy.…”
Section: Introductionmentioning
confidence: 99%